Partial discharge characteristics on nanocomposite-natural rubber blends as insulating material [electronic resource] - Muhammad Liwaunnasri Mohamad, 1988-, author; Yanuar Zulardiansyah Arief, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011